2020
DOI: 10.1038/s41598-020-71865-3
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A controls enteric neuron connectivity and is inversely associated with synapsin 1 expression in Hirschsprung disease

Abstract: Most of the gut functions are controlled by the enteric nervous system (ENS), a complex network of enteric neurons located throughout the wall of the gastrointestinal tract. The formation of ENS connectivity during the perinatal period critically underlies the establishment of gastrointestinal motility, but the factors involved in this maturation process remain poorly characterized. Here, we examined the role of Semaphorin 3A (Sema3A) on ENS maturation and its potential implication in Hirschsprung disease (HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…With the aim of studying the effects of Sema5A on enteric neuronal connectivity using in vitro ENS culture models, we first validated the expression of Sema5A and PlexinA1/A2 in a widely used ENS culture model derived from embryonic rat gut. 4 , 5 , 22 We found that Sema5A and Plexin A1/A2 were present in neurons, associated with both neuronal cell bodies and axonal processes, but not in glial cells, as observed in rat colon ( Figures 3 A–3C). These results indicated that the cellular expression and distribution of Sema5A and PlexinA1/A2 in ENS in vitro model derived from embryonic rat gut were similar to those in gut tissue.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…With the aim of studying the effects of Sema5A on enteric neuronal connectivity using in vitro ENS culture models, we first validated the expression of Sema5A and PlexinA1/A2 in a widely used ENS culture model derived from embryonic rat gut. 4 , 5 , 22 We found that Sema5A and Plexin A1/A2 were present in neurons, associated with both neuronal cell bodies and axonal processes, but not in glial cells, as observed in rat colon ( Figures 3 A–3C). These results indicated that the cellular expression and distribution of Sema5A and PlexinA1/A2 in ENS in vitro model derived from embryonic rat gut were similar to those in gut tissue.…”
Section: Resultssupporting
confidence: 58%
“…The precise mechanisms governing enteric neuronal connectivity as well as molecules involved in these processes remain poorly characterized. However, different classes of molecules, including transcription factors, 2 planar cell polarity pathways, 3 and axonal guidance molecules 4 , 5 have been shown to regulate ENS connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This group of affected genes contains known neuronal markers like ASCL1, NF1 , and PLXNA2 etc. It is noteworthy that PLXNA2 is a receptor for SEMA3A, whose role in in the migration of enteric neural crest cells is well documented (Anderson, Bergner et al 2007, Gonzales, Le Berre-Scoul et al 2020). Moreover, multiple members of the Semaphorin class 3 genes, including SEMA3A , harbor pathogenic variants in HSCR as well (Luzon-Toro, Fernandez et al 2013, Jiang, Arnold et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation identified in HSCR cohorts [48,69,70,121] Delays entry of axons and sacral ENCCs into the hindgut. Control neurons connectivity and migration [122,123,124].…”
Section: Sema3a Sema3c Sema3dmentioning
confidence: 99%